Navigating the storm: a young woman’s battle with refractory lupus nephritis complicated by pulmonary tuberculosis: a detailed case report - K., Gokul; V., Ramachandran; K., Shanmuganandan (International Journal of Research in Medical Sciences, 2025)
Systemic lupus erythematosus (SLE) is an autoimmune disease that is commonly treated with high dose of corticosteroids and other immunosuppressive medications. Patients with SLE are thus more likely to become infected with a variety of pathogens, including Mycobacterium tuberculosis. There are no established guidelines for treatment of tuberculosis in SLE patients with high disease activity due to a lack of relevant studies and management based on physician expertise. This article presents a case report of a 31 years old female with underlying SLE and refractory lupus nephritis previously treated with IV methylprednisolone pulse therapy and 6 doses of cyclophosphamide and Rituximab presented with Fever, cough with expectoration, pain abdomen and loose stools for a 15 days duration. Mini-BAL CBNAAT detected TB. She was treated with intravenous methylprednisolone and anti-tuberculous therapy, but the result was a fatal outcome.